EFFECT OF GAS NITRIDING PARAMETERS ON THE MICRO-HARDNESS OF HIGH-SPEED STEEL-CUTTING TOOLS - Al-Saraireh, Falah Mustafa; Suhymat, Shatha (Journal of Applied Engineering Science, 2024)
In this study, the nitriding parameters, such as nitriding time, nitrogen flow, and cooling type, were regularly modified to assess the effects of each on the microhardness of tools constructed of high-speed steel designed for commercial usage. The nitriding temperature was maintained at 670 °С for all of the tools. The tools were designed to measure microhardness. With a maximum value of 2000 HV at a time of 42 hours, direct nitriding with a nitrogen flow of 20 l/h and air cooling exhibits an apparent relationship between nitriding time and microhardness. The maximum microhardness value (1555.44 HV) was achieved by quenching after nitriding for 72 hours with a nitrogen flow rate of 20 l/h. The relationship between nitrogen flow and microhardness is semi-direct for direct nitriding at a nitriding duration of 30 hours and furnace cooling, with a maximum value of 1566.65 HV at a nitrogen flow of 110 l/h. The maximum microhardness was 2000 HV, with a 1.63% increase. The microstructure of the tools was improved by increasing the concentration of iron nitride in the ferrite cell, which means that the gas nitriding process increases the efficiency of cutting operations and reduces workpiece material surface roughness, based on the results of this study, it is advised to use high-purity nitrogen rather than ammonia. high-purity nitrogen gives better results than traditional nitriding using ammonia gas.
Keywords: nitriding, microhardness, machining operations, cutting tool, heat treatment